2017
DOI: 10.1002/art.40018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydroxychloroquine in Patients With Cutaneous Lupus Erythematosus: A Multicenter, Double‐Blind, Randomized, Parallel‐Group Trial

Abstract: Objective. To assess the efficacy and tolerability of hydroxychloroquine (HCQ) in patients with cutaneous lupus erythematosus (CLE), in a phase III clinical trial conducted in Japan.Methods. We conducted a double-blind, randomized, parallel-group clinical trial. This was a baselinecontrolled study, and the group differences were evaluated in an exploratory analysis. A total of 103 patients with active CLE (according to a Cutaneous Lupus Erythematosus Disease Area and Severity Index [CLASI] activity score of ‡4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 28 publications
0
86
1
3
Order By: Relevance
“…It may be a reactive allergic phenomenon associated with an imbalance in the immune system in an early stage after the initiation of HCQ . We summarize the characteristics of 21 reported cases of LE with cutaneous reactions due to HCQ, including our case, in Table . There were 11 cases of SLE (52.38%), eight of CLE (38.1%) and 2 of discoid lupus erythematosus (9.52%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It may be a reactive allergic phenomenon associated with an imbalance in the immune system in an early stage after the initiation of HCQ . We summarize the characteristics of 21 reported cases of LE with cutaneous reactions due to HCQ, including our case, in Table . There were 11 cases of SLE (52.38%), eight of CLE (38.1%) and 2 of discoid lupus erythematosus (9.52%).…”
Section: Discussionmentioning
confidence: 97%
“…Hydroxychloroquine (HCQ) is an antimalarial drug that has been widely used in the treatment of lupus erythematosus (LE) for more than 50 years. Although HCQ is generally tolerated better than other disease‐modifying drugs, it may still cause some adverse effects, including cutaneous toxicities, which lead to its cessation in some patients . After the initiation of this drug, an early adverse cutaneous eruption and an uncontrolled LE‐induced eruption usually share some similarities of symptoms; therefore, it is important to distinguish these two cutaneous eruptions in clinical practise.…”
Section: Introductionmentioning
confidence: 99%
“…The patient who had a history of chronic urticaria also complained about urticarial reaction more frequently 3 weeks later, which was improved with epinastine (10 mg daily) combination. The primary end point was judged by the change in the cutaneous lupus erythematosus disease area and severity index (CLASI) activity score following of HCQ treatment [2][3][4] . The CLASI activity score improved from 11 to 5 for 3 months.…”
Section: Case Reportmentioning
confidence: 99%
“…However, since it is too old drug, there are few scientific evidences and a very small number of mechanisms. A few years ago, we reported a multi-center, double-blind, randomized, parallel-group trial of HCQ in Japanese [2] . Since almost 2 years passed, this case report focused side effects especially urticaria.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Japan, HCQ followed the same fate as chloroquine even though there were no clinical experiences. Recently, nationwide clinical trials on the efficacy and safety (multicenter randomized control trial) were performed and excellent results were reported [5] . Interestingly, this report is the first clinical trial oriented for the approval because HCQ is very old and was approved in 1955 in the United States of America.…”
mentioning
confidence: 99%